Competency Analysis of Basic Education Teacher Candidates / Analisis Kompetensi Calon Guru Pendidikan Dasar - Sarah Fazilla; Edy Surya (Al-Mudarris: Journal Of Education, 2023)
This study aims to analyze the competence of prospective teacher students after the covid 19 pandemic. The method used is review systematic in accordance with Preferred reporting Items for Systematic Reviews and Meta-Analyses (PRISM). Search process focused on article journal about " Post-Pandemic Post-Pandemic Student Teacher Candidate Analysis Abilities " and " Post-Pandemic Student Teacher Competency which will be published in 2021 - 2022. The results of the research show that the quality and competence of student teacher candidates has decreased, this is especially in terms of pedagogy and ability appropriate technology integration. Therefore, there is a need for support in the form of policies that can be implemented by tertiary institutions through faculties in the field of education related to changes in the education system based on blended learning or hybrid learning.